Elaboration of PCDTBT nanorods and nanoflowers for augmented morphological and optical properties - Bakar, N.A.; Supangat, A.; Sulaiman, K. (Elsevier, 2014)
In the present study, the synthesis of p-type conducting polymer of poly[N-9′-hepta-decanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′ benzothiadiazole)] (PCDTBT) nanorods and nanoflowers are reported. PCDTBT nanorods and nanoflowers are formed via porous alumina template with different solution concentrations of 5 and 15 mg/ml, respectively. Two distinct nanostructures of nanorods and nanoflowers have portrayed the dissimilarity in their morphological and optical properties. PCDTBT solution has been infiltrated into the porous channel and replicated the inner porous channel. If compared to the PCDTBT nanorods, UV–vis and PL spectra of PCDTBT nanoflowers shows a wider peak and significant red-shifted. The changes in Raman shift are also observed which indicate the perfection of molecular structure arrangement in PCDTBT nanoflowers.